Q. 395.0( 2 Votes )

If we add 1 to th

Answer :

Let the fraction be

Case I



x + 1 = y – 1


x – y = -2 (1)


Case II



2x = y + 1


y = 2x -1 (2)


Substitute (2) in (1)




tx = 3


x = 3


put x = 3 in q(1)


3 – y = -2


y = 5


fraction =


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

<span lang="EN-USMathematics - Board Papers

A father&rsMathematics - Board Papers

Find the value ofRS Aggarwal - Mathematics

Find the value ofRS Aggarwal - Mathematics

A man purchased 4RS Aggarwal - Mathematics